Peningkatan Kemampuan Pedagogik Digital Pendidik melalui PDCA dalam MGMP Masa Covid-19 - Parimpunan Parimpunan (Jurnal Lingkar Mutu Pendidikan, 2021)
The lack of mastery teachers' digital pedagogical competences which has an impact to tasks, functions. This research 4 months, February to April 2020-2021, 5 subject groups 3 cycles, 3 meetings and 4 activities for: Planning, Action, Observation and Reflection. Uniqueness of educators, is reflected in cycle I, digital identification of real teacher, cycle II to III, in results in cycle I to II have increased 8%, cycle II to III has increased 8% so cycle III to I has increased 16%. Completeness increased from cycle I to II 8% and cycle II to III 36% so that cycle III to I was 44%. Judging remedial cycle I to II increased 17% and cycle II to III increased 3% so that cycle I to III 20%. The results of this indicate that the teacher's, can improve the digital pedagogical competence, relevant research to improve effectiveness of quality control